Trends and Challenges of Digital Transformation in the Public Sector: Policy Implications for Improving Public Services in Indonesian - Fitriani, Fitriani; Nurmandi, Achmad; Lawelai, Herman; Kasiwi, Aulia Nur; Younus, Muhammad (Universitas Muhammadiyah Ponorogo, 2025)
This research explores trends, challenges and innovations in digital transformation in the public sector, with a focus on its implications in Indonesia. The objectives of this study are to evaluate operational efficiency improvements in public services generated by digital transformation, identify challenges in the implementation of digital technologies, and provide policy recommendations to ensure the sustainability of technology adoption in the Indonesian public sector. The methodology used included a literature review and data analysis from the Scopus database, which was analyzed using VOSviewer to identify key patterns and trends in digital technology adoption in the public sector. The results show that the success of digital transformation depends not only on the adoption of new technologies, but also requires structural changes and organizational culture. Key challenges include resistance to change, the digital divide between urban and rural areas, and infrastructure limitations. This research provides policy recommendations that can accelerate the adoption of digital technologies in Indonesia, particularly through cross-sector collaboration and infrastructure improvements. The findings are expected to serve as a reference for policymakers and practitioners to strengthen the digitalization of public services in a sustainable manner. This research still has several limitations, such as the absence of field studies that directly test the effectiveness of digital transformation in the public sector, as well as analysis of regulations and human resource readiness that still need to be deepened. In addition, the mapping of digitalization trends in Indonesia is still limited to secondary data. For this reason, future research is recommended to conduct surveys or direct interviews with policy makers, strengthen policy analysis, and compare the implementation of digital transformation in other countries so that the strategies formulated are more appropriate and contextual for Indonesia.